COST AND TIME ANALYSIS OF THE FAST FOOD RESTAURANT BUILDING CONSTRUCTION PROJECT IN PONTIANAK USING CRASHING METHOD - Alan Muin, Oskar Ezra; Tjendani, Hanie Teki; Witjaksana, Budi (Transpublika Publisher, 2024)
The construction project of the McD Pontianak building encountered significant challenges due to a tight schedule of 110 calendar days and unforeseen delays arising from the existing building's foundation. These delays led to a setback in the construction progress, prompting the need for strategic measures to accelerate the project and mitigate the delays amounting to 11.48%, equivalent to 12.63 days. The potential financial consequences of this delay were estimated at IDR 228,366,605. In order to expedite the construction process, the chosen acceleration method was the crashing method, involving an increase in overtime ranging from 1 to 4 working hours, in accordance with relevant laws and regulations. This required a comprehensive analysis encompassing normal cost, normal duration, critical path, productivity, crashing cost, and crashing duration calculations. Upon thorough examination, it was determined that the optimal solution to overcome the delays was to implement an additional 2 hours of overtime. However, this decision came with associated costs, resulting in a necessary expenditure of IDR 93,651,965 to achieve a crashing time of 18.30 days. Despite the increased financial commitment, this strategic approach was deemed essential to meet the project's original schedule and avoid potential penalties. The findings and conclusions drawn from this analysis provide valuable insights into effective project management and decision-making in the face of unexpected challenges in the construction industry.